Affinity and kinetics of the interaction between soluble trimeric OX40 ligand, a member of the tumor necrosis factor superfamily, and its receptor OX40 on activated T cells. - Al-Shamkhani, A; Mallett, S; Brown, M; James, W; Barclay, A (1997)
OX40 ligand (OX40L) and OX40 are members of the tumor necrosis factor and tumor necrosis factor receptor superfamilies, respectively. OX40L is expressed on activated B and T cells and endothelial cell lines, whereas OX40 is expressed on activated T cells. A construct for mouse OX40L was expressed as a soluble protein with domains 3 and 4 of rat CD4 as a tag (sCD4-OX40L). It formed a homotrimer as assessed by chemical cross-linking and gel filtration chromatography. Radiolabeled sCD4-OX40L bound to activated mouse T cells with a high affinity (KD = 0.2-0.4 nM) and dissociated slowly (koff = 4 x 10(-5) s-1). The affinity and kinetics of the OX40L/OX40 interactions were studied using the BIAcoreTM biosensor, which measures macromolecular interactions in real time. The extracellular part of the OX40 antigen was expressed as a soluble monomeric protein and immobilized on the BIAcore sensor chip. sCD4-OX40L bound the OX40 with a high affinity (KD = 3.8 nM), although this was lower than that determined on the surface of activated T cells (KD = 0.2-0.4 nM), where there is likely to be less restriction in mobility of the receptor. In the reverse orientation, sOX40 bound to immobilized sCD4-OX40L with a stoichiometry of 3.1 receptors to one ligand, with low affinity (KD = 190 nM) and had a relatively fast dissociation rate constant (koff = 2 x 10(-2) s-1). Thus if the OX40 receptor is cleaved by proteolysis, it will release any bound ligand and is unlikely to block re-binding of ligand to cell surface OX40 because of the low monomeric affinity.